(3JhGUd GdMVGQGJ hGdEYdGe GdQbejs (3OQGSI GdhGbY hGdeSJbHd aj HjFI GdEYdGe GdQbej (B2021s - (3eYRI(B, (3eUWai CMeOs ((3YeGf(B;(3YeGfs (3OGQ CSGeI ddfTQ hGdJhRjY(B;(3fHdGA fGTQhf hehRYhf s, 2022)
(3GdEYdGe GdQbej, eGgjI GdEYdGe GdQbej, SeGJ GdEYdGe GdQbej, GdYdGbI Hjf GdEYdGe GdQbej hGdJbdjOj, JcfhdhLjG GdEYdGe GdQbej hGdJMhdGJ GdcHQi, CfhGY GdEYdGe GdQbej, GdEPGYGJ GdQbejI, GdJdaRjhf GdQbej, GdUMGaI GdQbejI, ehGbY GdCNHGQ GdEdcJQhfjI, hSGFd GdEYdGe GdQbej, THcGJ GdJhGUd GdELJeGYj, GdeOhfGJ, GdehGbY GdEdcJQhfjI, UOGe GdMVGQGJ hGdJhGUd HjfgG, eaghe GdMVGQI, UOGe GdMVGQGJ hGdMhGQ HjfgG, GdJhGUd Hjf GdMVGQGJ(B.s
Keywords: (3GdEYdGe GdQbejs; (3GdMVGQIs; (3THcGJ GdJhGUd GdELJeGYjs; (3hSGFd GdEYdGes